Effect of Inertial and Kinetic Forces of a Soil–Pile–Structure System on the Behavior of a Superstructure Under Earthquake - Sun-Yong Kwon (Applied Sciences)
The seismic behavior of pile-supported structures is influenced by complex interactions between inertial force and kinematic force mainly drawn by soil properties and superstructure characteristics. This study aims to investigate the combined effects of inertial and kinematic interaction on the dynamic response of pile foundations under seismic loading. To achieve this, three-dimensional numerical simulations were conducted using FLAC3D, based on a bridge substructure model. A total of twelve analysis cases were developed by varying input seismic motion levels, soil relative densities, and pile cap masses. The results demonstrate that kinematic force effects become more dominant in dense soils as seismic intensity increases, resulting in greater velocity responses and internal forces in the pile cap. Meanwhile, inertial forces from heavier superstructures interacted with kinematic force effects in a resistive manner, particularly under embedded pile cap conditions. The displacement of pile foundations remained within serviceable limits in all cases, although structural demands would be elevated under certain conditions. These findings confirm the significance of accounting for both inertial and kinematic effects in seismic design and highlight the importance of site-specific soil conditions.